Sizing the neural transmission line: UWB antenna effects on action potentials across nerve diameters - Salleh, Azahari; Mohamad, Najmiah Radiah; Othman, Adib; Noor Azizi, Muhammad Syafiq (Seventh Sense Research Group, 2024)
Wireless communication devices emit Electromagnetic (EMT) radiation, which is now widely present in modern society. This has led to worries over its impact on human physiology, specifically the interaction between EMT and the human nervous system. The assessment of the influence of Ultra-Wideband (UWB) technology on neural signaling poses distinct issues. This study examines the impact of UWB technology on Action Potentials (APs) in nerve fibers, taking into account the transmission line characteristics of different nerve diameters in uniform human arm models across three age groups (7, 26, and 38 years old). Both flat and cylindrical geometric layouts were examined, encompassing nerve fiber sizes ranging from 0.2 to 1.0 mm. A UWB Coplanar Waveguide (CPW)-fed circular patch antenna was incorporated into the arm models at different positions and orientations. AP signals, produced utilizing Izhikevich's neuron model in MATLAB and simulated in CST software, exhibited notable disparities in AP signal distortion between flat and cylindrical models. The results indicate an inverse relationship between the diameter of nerve fibers and their susceptibility to UWB interference. Smaller diameter fibers show more substantial distortions in action potentials across all age groups, with younger individuals demonstrating greater susceptibility to UWB influence. Additionally, larger areas of exposure led to greater amplitudes of spike interference. The findings underscore the importance of employing accurate anatomical models when evaluating the effectiveness and safety of UWB devices in biomedical contexts. They offer valuable insights into the impact of neural transmission line sizing on UWB radiation interaction and stress the significance of taking into account the diversity of nerve fibers and age-related factors in future assessments of electromagnetic compatibility.